Peningkatan Motivasi Wirausaha pada Kelompok Ibu-ibu Aisyiyah PRA Tamantirto Selatan - Muchamad Imam Bintoro; Rita Kusumawati (Edumedia Solution, 2022)
The partner in this community service program is “PRA Aisyiyah Tamantirto Selatan”. In addition to routine activities, namely the Sunday morning recitation which took place at the Khoirul Ummi Kasihan Mosque, several activities were also organized by the management of PRA Tamantirto including encouraging its members to actively play a role in improving family welfare in the economic field, namely becoming an entrepreneur. The problem faced by partners is that some members do not yet have the motivation to become entrepreneurs. Members who already have a business, their business management capabilities are still limited/less. Another problem that appears is that members' financial literacy is still relatively low. To overcome these problems, several trainings were held, namely entrepreneurial motivation training, food processing training, business management training and the provision of production equipment grants. The result of this program is that all activities run smoothly, participants are actively involved, and participants' motivation to become entrepreneurs increases This is an open access article under the CC–BY-SA license.